Financialisation and work: New transdisciplinary insights from micro-level survey data - Sigrid Betzelt; Ana C. Santos; Cláudia A. Lopes (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
The paper examines the interdependencies of financialisation and working conditions by exploring the comparative findings of a micro-level survey on household income, household debt, and working conditions which was conducted in five European countries representing different institutional and socio-economic contexts (Sweden, Germany, the UK, Portugal, Poland). Referring to different strands of debate in economics and sociology in a transdisciplinary way, four hypotheses on the impact of financialisation on the worker-consumer nexus are selected and tested: 1) the social inequality thesis, 2) the debt-income compensation thesis, 3) the cultural transformation thesis, and 4) the disciplinary thesis. The findings reveal that, notwithstanding differences across the five countries, living conditions have worsened after the Global Financial Crisis for many households, with declining household incomes, higher household indebtedness to cover living expenses, and deteriorated working conditions. Surprisingly, the finance-work nexus has been more detrimental to low-income and non-standard workers in Germany and Poland. Hence, it is concluded that the impact of financialisation on well-being cannot simply be read from the size of national financial systems or the extent of household engagement with finance, nor from mainstream welfare regime typologies. Instead, to better understand these impacts we need to consider the more indirect influence of financialisation on labour market polarization and income distribution.
Keywords: D14; G01; I31; J50; J81; P16; 330; EU; financialisation; inequality; household debt; working conditions; labour market segmentation